1990
DOI: 10.1073/pnas.87.11.4103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic modification of tyrosine-185 on the proton pump and the blue-to-purple transition in bacteriorhodopsin.

Abstract: The retinylidene chromophore mutant (Y185F) of bacteriorhodopsin, in which Tyr-185 is substituted by phenylalanine, is examined and compared with wild-type bacteriorhodopsin expressed in Escherichia coli; both were reinstituted similarly in vesicles. The Y185F mutant shows (at least) two distinct spectra at neutral pH. Upon light absorption, the blue species (which absorbs in the red) behaves as if "dead" i.e., neither its tyrosine nor its protonated Schiff base undergoes deprotonation nor does its tryptophan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The experimental set up for obtaining the transient absorption at 405 and 296 + 5 nm is basically the same as described previously (31,32), except that the data acquisition and analysis were done by a personal computer. The extraction of the rate constant for both the rise and the decay of the M intermediate and the UV transient absorption were done by using a nonlinear least-square fitting computer program assuming biexponential rise or decay, with variable preexponential factors as shown below.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental set up for obtaining the transient absorption at 405 and 296 + 5 nm is basically the same as described previously (31,32), except that the data acquisition and analysis were done by a personal computer. The extraction of the rate constant for both the rise and the decay of the M intermediate and the UV transient absorption were done by using a nonlinear least-square fitting computer program assuming biexponential rise or decay, with variable preexponential factors as shown below.…”
Section: Methodsmentioning
confidence: 99%
“…Tables Table 1. Comparison of natural variation and introduced mutations in retinal-binding pocket of GR and homologs. E [53] N [53] V [54] S [54] T [55] F [56] A [57] D [58] N [59] V [60] A [61] V [61] A [62] T [62] V [62] A [26] -C [63] -C [60] A [26] C [57] V [57] A [63] F [56] F [64] A [65] L [66] V [60] F [67] E [68] N [26] T [26] - G [25] A [25] A [25] K [70] ---------H [25] N [25] --E [71] --a Homologous residues in the retinal-binding pocket were identified through structure-guided alignment of protein sequences. b Natural variation represents variants retrieved from BLAST searches of the NCBI database with GR, BR and PR.…”
Section: Figurementioning
confidence: 99%
“…It also suggested that Tyr185 in MR can interact with Asp213 or Thr216 via hydrogen bonding, e.g., Tyr174-Thr204 in Np SRII [ 43 ]. The conserved Tyr is an essential residue in the reaction center of microbial rhodopsins given that its mutants have a significant effect on the efficacy of the light-driven proton pump in BR or the light-induced signal transduction in Np SRII [ 11 , 44 ]. Further, given importance of the formation of the Tyr185-Thr215 hydrogen bond in the signal transduce-able BR mutant with respect to the expression of negative phototaxis [ 20 ], the hydrogen bond between Tyr185 and Thr216 in MR plays an essential role in the signal transduce-able mutant of MR [ 16 ].…”
Section: Resultsmentioning
confidence: 99%